Dietary acid load on the Mediterranean and a vegan diet: a secondary analysis of a randomized, cross-over trial - Kahleova, Hana; Maracine, Cristina; Himmelfarb, Joseph; Jayaraman, Arathi; Znayenko-Miller, Tatiana; Holubkov, Richard; Barnard, Neal D. (Frontiers in Nutrition, 2025)
BackgroundEvidence suggests that changes in dietary acid load may influence body weight, and the purpose of this secondary analysis was to assess its role in the context of the Mediterranean and a vegan diet in overweight adults.MethodsIn this randomized cross-over trial, 62 overweight adults were randomized to a Mediterranean or a low-fat vegan diet for 16-weeks, separated by a 4-week washout. Change in body weight was the primary outcome. Three-day dietary records were analyzed, and Potential Renal Acid Load (PRAL) and Net Endogenous Acid Production (NEAP) were calculated as markers of dietary acid load, and their relationship was tested with changes in body weight.ResultsCompared with no change on the Mediterranean diet, PRAL and NEAP significantly decreased on the vegan diet; effect sizes: −25.8 (95% CI −34.1 to −17.5); p < 0.001; and −27.1 (95% CI −35.4 to −18.7); p < 0.001, respectively. Across both diets, changes in PRAL and NEAP were positively associated with changes in body weight in the first 16 weeks of the study: r = +0.34; p = 0.009; and r = +0.39; p = 0.002, respectively, as well as in the second 16 weeks: r = +0.59; p < 0.001, and r = +0.61; p < 0.001, respectively.ConclusionThese findings suggest that, compared with the Mediterranean diet, dietary acid load decreased significantly on the low-fat vegan diet and was associated with weight loss. The alkalizing effect of a vegan diet may be an independent mechanism by which a vegan diet promotes weight loss.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT03698955.